Fracture of the Posteromedial Tubercle of the Talus: Surgical Approach With Case Examples. Issue 3 (18th September 2021) - Steffensmeier, Andrew M.; Matar, Robert; Chung, David; Dixon, Tonya; Laughlin, Richard
Abstract : Ten to 21% of talus fractures involve the posteromedial tubercle. A search query of the institutional database was performed for all adult patients that sustained talar fractures over an 8-year period. Fifteen of these patients had isolated fractures of the posteromedial tubercle. Seventy-three percent of the patients had an associated subtalar dislocation; in all of these, the fracture of the posteromedial tubercle was comminuted. Plain radiographs have been shown to lack sensitivity in detecting posterior process fractures, which includes posteromedial and posterolateral tubercles. In this group, 86% had initial plain radiographs that missed the fracture. This paper reviews the posteromedial tubercle fractures and fracture patterns to illustrate surgical strategies and approaches for open reduction and internal fixation. Exposures are described for access to the posteromedial tubercle and strategies for distraction and reduction are described. Level of Evidence: Diagnostic Level IV. See Instructions for Authors for a complete description of levels of evidence.